2005
DOI: 10.1016/j.immuni.2004.11.011
|View full text |Cite
|
Sign up to set email alerts
|

The KSHV Immediate-Early Transcription Factor RTA Encodes Ubiquitin E3 Ligase Activity that Targets IRF7 for Proteosome-Mediated Degradation

Abstract: Many viruses encode proteins that counteract the development of the interferon (IFN)-mediated antiviral state. Here, we report that interferon regulatory factor 7 (IRF7), a key mediator of type I IFN induction, is targeted for degradation by binding to the RTA immediate-early nuclear transcription factor encoded by Kaposi's sarcoma-associated herpesvirus (KSHV or HHV8). Cotransfection with RTA blocked IRF7-mediated IFNalpha and IFNbeta mRNA production and promoted the ubiquitination and degradation of IRF7 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
250
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(267 citation statements)
references
References 33 publications
16
250
0
1
Order By: Relevance
“…However, IFN production was still inhibited by RTA as reported previously (20). We have examined the mechanism of this IRF-7 degradation-independent IFN inhibition and found that RTA degrades cellular TRIF protein, an upstream adaptor protein involved in IFN production.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…However, IFN production was still inhibited by RTA as reported previously (20). We have examined the mechanism of this IRF-7 degradation-independent IFN inhibition and found that RTA degrades cellular TRIF protein, an upstream adaptor protein involved in IFN production.…”
supporting
confidence: 61%
“…Production-RTA has been shown to degrade cellular IRF-7 for the blockage of IFN production (20). We have examined whether RTA could degrade IRF-7 extensively and found that RTA was unable to degrade IRF-7 in the cell line we used (293T) (Fig.…”
Section: Rta Has An Additional Mechanism(s) To Block the Ifnmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whereas polyubiquitination on lysine 43 targets proteins for degradation, lysine 63 polyubiquitination is a signal for kinase activation. Many viruses modulate the Ub-proteasome pathway to alter cellular signaling and the antiviral response (14,15). HIV-1 uses ubiquitination at two steps of its replication cycle.…”
mentioning
confidence: 99%